Teaching and Learning of Computational Modelling in Creative Shaping Processes - Daniela REIMANN; Christiane MADAY (Ediciones Universidad de Salamanca, 2017)
Today, not only diverse design-related disciplines are required to actively deal with the digitization of information and its potentials and side effects for education processes. In Germany, technology didactics developed in vocational education and computer science education in general education, both separated from media pedagogy as an after-school program. Media education is not a subject in German schools yet. However, in the paper we argue for an interdisciplinary approach to learn about computational modeling in creative processes and aesthetic contexts. It crosses the borders of programming technology, arts and design processes in meaningful contexts. Educational scenarios using smart textile environments are introduced and reflected for project based learning.